The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1007/bf00172533
|View full text |Cite
|
Sign up to set email alerts
|

Waves and wave-particle interactions in the magnetosphere: A review

Abstract: Recent space observations of waves, both electromagnetic and electrostatic, are reviewed and the role which they can play in the dynamics of magnetospheric particles is stressed. Wave particle interactions (WPI) in the exo-and intra-plasmaspheric media depend on the exact process of particle injection under the influence of magnetospheric electric fields, and on the spatial distribution of the cold plasma particles; these two aspects of the problem are studied to some extent. The concepts of optimum cold plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 172 publications
0
30
0
Order By: Relevance
“…Using the experimental data they have further shown that the emissions depend on the increase in anisotropy rather than the increase in intensity of the energetic electrons in the plasmasheet. The importance of anisotropy in the distribution function in the generation of VLF hiss including pulsed hiss during the Doppler-shifted cyclotron resonance interaction was also recognized by the other workers (Etcheto et al, 1973;Gendrin, 1975, Ward, 1983.…”
Section: Generation Mechanismmentioning
confidence: 86%
“…Using the experimental data they have further shown that the emissions depend on the increase in anisotropy rather than the increase in intensity of the energetic electrons in the plasmasheet. The importance of anisotropy in the distribution function in the generation of VLF hiss including pulsed hiss during the Doppler-shifted cyclotron resonance interaction was also recognized by the other workers (Etcheto et al, 1973;Gendrin, 1975, Ward, 1983.…”
Section: Generation Mechanismmentioning
confidence: 86%
“…The interactions between electrons and right-handed (RH) whistler waves or between protons and left-handed (LH) Alfv~n waves are well known phenomena which are at the origin of the precipitation of both kinds of particles (i.e., Gendrin, 1970Gendrin, , 1972Gendrin, , 1975. Even the nonlinear phase of these interactions is now well documented, both experimentally and theoretically (i.e., Helliwell and Katsufrakis, 1978;Matsumoto, 1979).…”
Section: General Properties Of Gyroresonant Interactionsmentioning
confidence: 99%
“…An extensive literature, including dozens of reviews and monographs, has been accumulated in 70 years of experimental and theoretical investigations of the Pc1 waves (e.g., Troitskaya, 1964;Troitskaya andGuglielmi, 1967, 1969;Saito, 1969;Guglielmi and Troitskaya 1973;Guglielmi, 1974Guglielmi, , 1979Guglielmi, , 1989Gendrin, 1975;Nishida, 1978;Fraser, 1985;Anderson et al, 1992a, b;Pokhotelov, 1994, 1996;Kangas et al, 1998Kangas et al, , 1999 and lively discussions about the Pc1 origin and properties still continue (e.g., Johnson and Cheng, 1999;Mursula et al, 1999Mursula et al, , 2001Guglielmi et al, 2001;Loto'aniu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on the excitation of the Pc1 waves due to the ion cyclotron instability of energetic ions in the equatorial zone of the magnetosphere and the literature on the propagation of these waves along the geomagnetic field lines in the magnetosphere and along the Earth's surface in the ionospheric waveguide are voluminous (e.g., see the review papers and monographs by Troitskaya andGuglielmi, 1967, 1969;Gendrin, 1975;Nishida, 1978;Guglielmi, 1979;Pokhotelov, 1994, 1996;Kangas et al, 1998). At the same time, as often happens in a successfully developing field, there is a certain tendency to neglect some basic problems which seemed exceptionally important not long ago and which were actively discussed by the space physicists but nevertheless remained unsolved.…”
Section: Introductionmentioning
confidence: 99%